Transplantation of hepatitis C virus (HCV) antibody positive, nucleic acid test negative donor kidneys to HCV negative patients frequently results in seroconversion but not HCV viremia. Issue 10 (27th August 2018) - de Vera, Michael E.; Volk, Michael L.; Ncube, Ziphezinhle; Blais, Shawna; Robinson, Melissa; Allen, Nancy; Evans, Ryan; Weissman, Jill; Baron, Pedro; Kore, Arputharaj; Bratton, Charles; Garnett, Gwendolyn; et al.
Abstract : Anecdotal reports have suggested that transplantation of hepatitis C virus (HCV) antibody positive (Ab+)/nucleic acid test negative (NAT−) donor kidneys into HCV negative recipients is not associated with HCV transmission. We reviewed our center's outcomes of 32 HCV negative patients who received kidney allografts from 25 donors who were HCV Ab+/NAT−. The mean recipient age was 56.9 ± 12.1 years and the mean donor age was 41.5 ± 14 years, with a median Kidney Donor Profile Index (KDPI) of 68%. Twelve donors (48%) met Public Health Service (PHS) increased risk status. All patients received antithymocyte globulin induction followed by tacrolimus, mycophenolate mofetil, and steroid maintenance immunosuppression. With a mean follow‐up posttransplant of 10 ± 2.7 months, 1‐ and 3‐ month serum creatinine levels were 1.7 ± 0.8 and 1.3 ± 0.4, respectively, and patient and graft survival rates were 100% and 97%, respectively. Fourteen patients (44%) seroconverted and became HCV Ab+ posttransplant. However, all 32 patients were HCV RNA negative at 1‐ and 3‐ months posttransplant, and 27 and 8 patients tested at 6‐ and 12‐months posttransplant, respectively, remain HCV RNA negative. In conclusion, transplantation of HCV Ab+/NAT− kidneys to HCV negative recipients frequently causes HCV Ab seroconversion but not HCV viremia. Abstract : This single‐center study demonstrates the absence of HCV transmission when transplanting kidneys from HCV antibody positive/nucleic acid testing negative donors. See Goldberg and Wolfe's editorial onpage 2380 .